2022
DOI: 10.21037/gs-22-29
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal spindle-like microcephaly-associated protein promotes proliferation by regulating cell cycle in epithelial ovarian cancer

Abstract: Background: Epithelial ovarian cancer (EOC) ranks first for female gynecological tumor-related deaths.Due to the limited efficacy of traditional chemotherapy strategies, potential therapeutic targets are urgently needed. Previous studies have reported a relationship between abnormal spindle-like microcephalyassociated protein (ASPM) and ovarian cancer based on immunohistochemistry (IHC) and bioinformatics analysis. However, the potential role of ASPM in the proliferation of ovarian cancer cells and its molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Complete loss of BUB1B reduces ovarian function and fertility in female mice ( 42 ). ASPM is a spindle pole intermediate protein that regulates reproduction in female mammals ( 43 ). Loss of ASPM results in abnormal ovarian function while preventing folliculogenesis ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete loss of BUB1B reduces ovarian function and fertility in female mice ( 42 ). ASPM is a spindle pole intermediate protein that regulates reproduction in female mammals ( 43 ). Loss of ASPM results in abnormal ovarian function while preventing folliculogenesis ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of ASPM results in abnormal ovarian function while preventing folliculogenesis ( 44 ). Silencing ASPM causes cell cycle arrest and leads to apoptosis ( 43 ). This study found that ASPM was significantly higher in the estrous phase than in the luteal and pre-estrous phases, suggesting that ASPM may have an integral role in follicular development by regulating cell proliferation and the cell cycle.…”
Section: Discussionmentioning
confidence: 99%